2021
DOI: 10.1002/cctc.202100431
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Mn Promotion on HKUST‐1 Metal‐Organic Frameworks for Low‐Temperature Selective Catalytic Reduction of NO with NH3

Abstract: A series of HKUST-1 supported catalysts (also known as Cu-BTC, or -benzene-1,3,5-tricarboxylate]) modified with different loadings of manganese were synthesized and characterized by powder X-ray diffraction, scanning electron microscopy/energy dispersive spectroscopy, nitrogen sorption, thermogravimetric analysis, and temperature-programmed desorption with NH 3 . The structural and textural properties of the solids, compared to the reference support, are preserved as much as possible when the manganese content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Following this study, different loadings with Mn into HKUST-1 were tested. 129 It was investigated 2.5, 3.75, 5.0, 7.5, and 10.0 wt%, which HKUST-1-Mn(3.75) exhibits 68% conversion for NO x . The effect of Mn species was related to the localization within the framework since Mn clusters were mapped inside and outside the crystal, leading to facile access to the material.…”
Section: Greenhouse Gasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Following this study, different loadings with Mn into HKUST-1 were tested. 129 It was investigated 2.5, 3.75, 5.0, 7.5, and 10.0 wt%, which HKUST-1-Mn(3.75) exhibits 68% conversion for NO x . The effect of Mn species was related to the localization within the framework since Mn clusters were mapped inside and outside the crystal, leading to facile access to the material.…”
Section: Greenhouse Gasesmentioning
confidence: 99%
“…The effect of Mn species was related to the localization within the framework since Mn clusters were mapped inside and outside the crystal, leading to facile access to the material. 129…”
Section: Greenhouse Gasesmentioning
confidence: 99%
“…The authors suggest that the combination of proper pore sizes, enhancement of redox activity via incorporation of Mn 4+ ions, and the synergistic effect between Mn 2+ and Cu 2+ results in superior DeNO x performance . The commercial HKUST-1 (Basolite C300) was examined under NH 3 -SCR conditions in the studies of Świrk et al , During the pretreatment step carried out in helium from 145 to 250 °C, the authors observed a gradually increasing formation of carbon dioxide with a heating ramp, highlighting the crucial role of the temperature. The temperature of 185 °C is recognized as the highest possible and carbon-free experimental adjustment, allowing the authors to prevent a partial decomposition of the organic framework.…”
Section: Catalytic Reduction Of No Xmentioning
confidence: 99%
“…After stabilizing the activity values, the NO and NH 3 conversions are reported to be 78% and 73%–84%, respectively. Different loadings of Mn (2.5, 3.75, 5.0, 7.5, and 10.0 wt %) were analyzed, and structural and textural modifications were evidenced by the creation of new mesopores . According to the authors, the mesoporosity could promote, to some extent, the diffusion properties, allowing easy access of molecules to enhance the catalytic activity in the NH 3 -SCR process.…”
Section: Catalytic Reduction Of No Xmentioning
confidence: 99%
See 1 more Smart Citation